Prenatal care among rural to urban migrant women in China - Zhanhong Zong; Jianyuan Huang; Xiaoming Sun; Jingshu Mao; Xingyu Shu; Norman Hearst (BMC, 2018)
Abstract Background There is a very large population of internal migrants in China, and the majority of migrant women are of childbearing age. Little is known about their utilization of prenatal care and factors that influence this. We examined this using data from a large national survey of migrants. Methods 5372 married rural to urban migrant women aged 20-34 who were included in the 2014 National Dynamic Monitoring Survey on Migrants and who delivered a baby within the previous two years were studied. We examined demographic and migration experience predictors of prenatal care in the first trimester and of adequate prenatal visits. Results 12.6% of migrant women reported no examination in the first trimester and 27.6% had less than 5 prenatal visits during their latest pregnancy. Multivariate analysis indicated that demographic predictors of delayed and inadequate care included lower educational level, lower income and not having childbearing insurance. Migrating before pregnancy, longer time since migration, having migrated a greater distance, and not returning to their home town for delivery were correlated with better prenatal care. Conclusions Many internal migrant women in China do not receive adequate prenatal care. While internal migration before pregnancy seems to promote adequate prenatal care, it also creates barriers to receiving care. Strategies to improve prenatal care utilization include expanding access to childbearing insurance and timely education for women before and after they migrate.